The formative years of a biologist at “Institutul de Speologie Emil Racoviţă” [Emil Racovitza Institute of Speleology] - DAN L. DANIELOPOL (Travaux de l'Institut de Speologie Emile Racovitza, 2021)
A brief biographic sketch of the author’s scientific education and the research activities at “Institutul de Speologie EmilRacoviţă” is presented. The text is offered as an homage to the centennial anniversary of this institution with its important contributionto the Romanian cultural activities (1920–2020)